Thermal performance improvement of a radial heat sink with a hollow cylinder for LED downlight applications. (October 2015) - Park, Seung-Jae; Jang, Daeseok; Lee, Kwan-Soo
Highlights: A cooling system consisting of a hollow cylinder and a radial heat sink is studied. A hollow cylinder installment improves thermal performance of the radial heat sink. Effects of hollow cylinder's installment environment are studied. Abstract: A cooling system consisting of a hollow cylinder and a radial heat sink that can be applied to a light-emitting diode (LED) downlight is suggested. Natural convection heat transfer is simulated via a numerical model and validated experimentally. The airflow pattern around the radial heat sink is similar to that of a chimney, entering from the side of the heat sink and moving upward. When the hollow cylinder is installed, the mass flow rate of air to the heat sink fins increases, which results in enhanced thermal performance of the heat sink. The effect of the size, set up height and material of the hollow cylinder is analyzed, and the performance of heat sinks with various fin-types is calculated. The results show that the thermal performance of a radial heat sink is enhanced by up to 43% following installation of a hollow cylinder.